Seizing the white space : business model innovation for growth and renewal - Johnson, Mark W. (Boston, Mass : Harvard Business, 2010)
Johnson focuses not so much on the development of new technologies and products as on the implementation of new business models. A successful business model depends on four aspects--a customer value proposition (CVR), a profit formula, and the key resources and processes that need to be in place in order to deliver value to the custstomer. Building on this simple model, Johnson explores, using a number of case studies, how companies can move into transforming existing markets, creating new markets, and emerging in a strong posisition from times of industry upheaval.
Includes bibliographical references and index.
Keywords: Diversification in industry -- Management; Business planning; New products